The Effect of Social Media Usage and Market Orientation on Marketing Performance - Romadhon, Ali Mas’ud; Suyono, Suyono (Jurnal Ilmiah Manajemen Kesatuan, 2024)
MSMEs in Indonesia have not developed optimally due to a lack of understanding of digital technology and appropriate marketing strategies amidst fierce competition. To be successful, MSMEs need knowledge about digitalization and effective marketing. This study aims to examine the effect of social media usage and market orientation on MSME marketing performance, with business actors in Kamal District, Bangkalan as the object, both online and offline. The study used a quantitative method with accidental sampling techniques and multiple linear regression analysis using SPSS. The results show that partially, the use of social media and market orientation each have a positive and significant effect on marketing performance. Simultaneously, both also have a positive and significant effect on MSME marketing performance. This study emphasizes the importance of social media and market orientation in increasing the competitiveness and performance of MSMEs in the digital era.